OP0034 The association between radiographic hand osteoarthritis and meniscal damage on MRI in the general population. (23rd January 2014) - Englund, M.; Haugen, I.K.; Guermazi, A.; Roemer, F.W.; Niu, J.; Neogi, T.; Aliabadi, P.; Clancy, M.; Felson, D.T.
Abstract : Background: Meniscal damage is a potent risk factor for the development and progression of knee osteoarthritis (OA). However, studies addressing the possible cause(s) of meniscus lesions are sparse. Objectives: To gain new insights into whether radiographic hand OA, a possible biomarker of general OA susceptibility, is associated with meniscal damage. Methods: We studied 974 subjects (56.9% women, 92.9% Caucasians) between 50 and 90 years of age drawn via census tract data and random-digit dialing from Framingham, MA, USA. Selection was not based on knee, hand, or other joint problems. One reader (IKH) assessed bilateral hand radiographs (distal interphalangeal, first interphalangeal, proximal interphalangeal, metacarpophalangeal, and the first carpometacarpal/scaphotrapezial joint) according to the Kellgren and Lawrence (KL) scale (a total of 30 joints). Another reader (ME) assessed right knee 1.5T MRI scans for meniscal integrity in the anterior horn, body, or posterior horn of the medial and lateral meniscus. A third reader (PA) graded all frontal knee radiographs obtained by semi-flexed weight-bearing fixed-flexion protocol according to the KL scale. All readers were blinded to the other readings and clinical data. We divided the sample into three groups based on the number of finger joints with radiographic OA (KL grade ≥2). We then calculated the odds of having meniscal damage (i.e., tear or maceration/destruction) in at least one subregion of either the medial and (or) the lateral meniscus in those with 1 to 2 and ≥3 OA finger joints, respectively, as compared to those with no OA finger joints (logistic regression with adjustment for age, sex and body mass index). We also evaluated the above association in subjects with KL grade 0 in their right knee (n=749), i.e., excluding all knees with evidence of radiographic structural findings suggesting tibiofemoral OA (KL grade ≥1). Results: The proportion of subjects in the study sample (n=974) without radiographic OA in the finger joints was 35.0%, while radiographic OA in 1 to 2, and ≥3 finger joints was present in 27.8% and 37.2%, respectively. The prevalence of a meniscal damage in one or more locations on MRI of the right knee according to number of finger joints with OA (grouping as above) was 24.9%, 31.7%, and 47.2%, respectively. The odds of having meniscal damage was significantly increased if having 3 or more finger joints affected by radiographic OA, and the adjusted estimate remained similar in knees with KL grade 0 (n=749). Conclusions: Having multiple finger joints with radiographic OA is associated with meniscal damage of the knee. The results suggest a common systemic/genetic predisposition and (or) a common environmental risk factor for radiographic hand OA and meniscal damage in the middle-aged and elderly. Disclosure of Interest: None Declared